Faktor-Faktor yang Mempengaruhi Sikap Remaja Putri tentang Flour Albus di SMP Negeri 2 Trucuk Kabupaten Klaten - Susiana Sariyati (Alma Ata University Press, 2014)
Flour albus is a discharge excessive that causes an adolescent girls often replace the underwear or using a bandage. Less of knowledge about flour albus may impact on adolescent girls negative attitude or less attention about flour albus. The purpose of this study was to find the factors that affected adolescent girls attitude about flour albus in Trucuk 2 Junior High School District Klaten. Study design used in this study was cross sectional. The population of 9th grade adolescent girls were 120 female students. The samples of this study were 92 adolescent girls that already menstruation. Samples were selected by simple random sampling technique. The results showed that most of adolescent girls had a good knowledge. The factors that most affected adolescent girls attitude was knowledge supported by information and experience. In conclusion, there was a significant relationship between knowledge and attitude, there was a significant relationship between experience and attitude, there was a significant relationship between source of information and attitude.